Peranan Kompolnas Dalam Mendukung Upaya Optimalisasi Penegakan Hukum Oleh Polri Terhadap Kejahatan Konvensional Menonjol di Indonesia - Syahrir Kuba (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Crime is the shadow of human civilization. So far, the trend of the development of prominent conventional crimes (crime index) in Indonesia tends to increase while the implementation of law enforcement is still not optimal. Against this condition, it is necessary to investigate various factors related to the effectiveness of conducting investigations and investigations into prominent conventional crimes committed by members of the National Police Investigation Unit, including legal substance, legal structure, and legal culture. The National Police Commission (Kompolnas) can request data and information from members and officials within the National Police, government agencies, the public, or other parties deemed necessary to support the implementation of the main tasks of the National Police in the field of law enforcement in Indonesia. However, even though Kompolnas have carried out this role, it is not yet fully optimal due to the wide scope that must be handled, so it has not been able to touch/monitor to regional units such as Polres and Polsek in supporting law enforcement by the Police through investigation and investigation activities against Conventional crimes stand out. With the existing limitations, Kompolnas needs to increase its role in monitoring law enforcement by the Police through means of communication in the form of an online computer and have regional maps related to the characteristics of regional vulnerabilities in the field of security and social security and maps of budgetary requirements and other resources. In addition, Kompolnas also plays an important role in encouraging the leaders of the National Police to properly organize and dynamic the data collection system for prominent conventional criminals that already exists in the Investigation Unit, starting from the Directorate of Criminal Investigation of the Regional Police to the Criminal Investigation Unit of the Polsek/ta by using computers/information technology.